Resveratrol, a SIRT1 Activator, Ameliorates MK-801-Induced Cognitive and Motor Impairments in a Neonatal Rat Model of Schizophrenia - Niu, Juan; Cao, Yuquan; Ji, Yongjuan (Frontiers in Psychiatry, 2020)
Background: In neonatal rats, MK-801 treatment generates schizophrenia-like symptoms. Resveratrol (RSV) is a phenolic compound and a potent neuroprotective agent. This research aimed to illustrate the effect of RSV on the amelioration of MK-801-induced cognitive and motor impairments in a neonatal rat schizophrenia model and the related potential molecular changes. Methods: Rats were administrated with MK-801, MK-801 + RSV (40 mg/kg), or MK-801 + RSV (80 mg/kg). Motor learning, coordination, locomotor and exploratory activity, and spatial memory were measured by rotarod test, pen field test, and Morris water maze test. Relative protein levels were analyzed by Western blot and ELISA. mRNA levels were shown by qRT-PCR. Results: In the hippocampus of MK-801-induced schizophrenia rat model, RSV enhanced silent information regulator 1 (SIRT1) and brain derived neurotrophic factor (BDNF) expression and alleviated oxidative stress. Motor perturbations and learning impairments by MK-801 treatment were ameliorated by the administration of RSV. Conclusion: In conclusion, RSV showed neuroprotective effect on MK-801-induced schizophrenia rat model through regulating SIRT1 and downstream BDNF expression in the hippocampus.